Malaysia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The report provides the IMF's projections and estimates on Malaysia's federal government revenue and grants, and fiscal operations, 1998-2003, economic classification of federal government, labor market developments, operations of state and local governments during 1998-2003, operations of the employee's provident fund, funds raised in the capital market, 1998-2002, developments in Malaysian exchanges, 1998-2002, oil and LNG trade, direction of trade, international reserves, commodity exports, balance of payments, summary of external debt and debt services during 1997-2002, interbank swap transactions, 1998-2003, financial account, services account during 1999-2002, and so on.